GAMIFYING VOCABULARY LEARNING: THE EFFECTS ON STUDENTS’ ACQUISITION - Indah Lestari; Desi Surlitasari Dewi; Shalehoddin Shalehoddin (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2024)
Vocabulary acquisition is a critical aspect of language learning, yet traditional teaching methods often fail to engage students. Game-based learning (GBL), particularly using platforms like Kahoot, has emerged as a promising approach to address these challenges by fostering an engaging and interactive learning environment. This study aims to investigate the effectiveness of GBL, specifically using Kahoot games, in improving vocabulary acquisition and enhancing student engagement among 7th-grade students. A mixed-method approach was employed, combining quantitative analysis of pre-test and post-test scores with qualitative insights gathered from student interviews and classroom observations. With a mean difference of -26.000, t = -17.085, and p = 0.000, the paired sample t-test findings indicate a significant increase in post-test scores compared to pre-test scores and 0.9150 is the mean N-Gain score. The study suggests that integrating educational games like Kahoot into the classroom can effectively enhance vocabulary acquisition and create an engaging learning environment. so that the implementation of Game-Based Learning based on Kahoot games can be applied according to current conditions and can be more optimal in the future.